AN ANALYSIS OF THE TYPES AND FUNCTIONS OF AGNEZ MO’S CODE-MIXING ON DEDDY CORBUZIER’S PODCAST (The GIST, 2024)
Code-mixing is now widely used in social media because of developments over time. Especially public figures, use Code-mixing to gain prestige. This analysis aims to find out the types and functions of Agnez Mo’s Code-mixing on Deddy Corbuzier’s podcast. This data analysis uses Muysken’s and McKay's theory and the author uses qualitative descriptive methods. The data source consists of a transcription of Agnez Mo’s speech on Deddy Corbuzier's podcast, and the object of this research is the type and function of speech. Data analysis uses several techniques, namely: classifying, interpreting, and making conclusions. The result of the analysis shows the type of Code-mixing they are insertion had the 2 data, alternation of 2 data, and congruent lexicalization 2 data. Then, the function of Code-mixing with identity marking is 2 data, stylistic is 1 data and Socio-expressive is 4 data. It can become a style out of habit. Code-mixing is also used when making a joke. And the last thing is to express one's emotions. The researcher only took a few examples of data from the large amount of data, because almost all of them had the same pattern.